2008
DOI: 10.1021/ja077141m
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Metal Ion Selectivity of 2,9-Di-(pyrid-2-yl)-1,10-phenanthroline and Its Use as a Fluorescent Sensor for Cadmium(II)

Abstract: The metal ion complexing properties of the ligand DPP (2,9-di-(pyrid-2-yl)-1,10-phenanthroline) were studied by crystallography, fluorimetry, and UV-visible spectroscopy. Because DPP forms five-membered chelate rings, it will favor complexation with metal ions of an ionic radius close to 1.0 A. Metal ion complexation and accompanying selectivity of DPP is enhanced by the rigidity of the aromatic backbone of the ligand. Cd2+, with an ionic radius of 0.96 A, exhibits a strong CHEF (chelation enhanced fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(156 citation statements)
references
References 63 publications
8
147
1
Order By: Relevance
“…This phenomenon is known in the literature as "chelation-enhanced fluorescence (CHEF)" and is in most cases due to the suppression of low-lying charge-transfer transitions upon metal binding. 13 A preliminary solvent screening revealed that the emission efficiency for all complexes was generally high in relatively unpolar solvents (such as CHCl 3 , toluene, THF, etc.) and decreased in more polar media such as DMF and CH 3 CN.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…This phenomenon is known in the literature as "chelation-enhanced fluorescence (CHEF)" and is in most cases due to the suppression of low-lying charge-transfer transitions upon metal binding. 13 A preliminary solvent screening revealed that the emission efficiency for all complexes was generally high in relatively unpolar solvents (such as CHCl 3 , toluene, THF, etc.) and decreased in more polar media such as DMF and CH 3 CN.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…14 For example, it has been reported that the pre-organized, phenanthroline-based ligand 2 15 exhibits higher levels of complex stability and selectivity towards Cd(II) than related ligands such as quaterpyridine. 16 In addition, phenanthrolines have larger dipole moments than the 2,2'-bipyridines, 17 and often coordinate strongly to water via hydrogen bonding. 18 These properties could lead to improved extraction kinetics in a separation process since the ligand may interact more favourably with the organic/water interface.…”
Section: Introductionmentioning
confidence: 99%
“…After heating at reflux for one hour to ensure complete solution of the PDOX, and storage for a few days, colorless crystals of 1 precipitated out. C 18 …”
Section: Methodsmentioning
confidence: 99%
“…Familiar examples of preorganized ligands are crown ethers, [12] cryptands, [13] and nitrogen-donor (Ndonor) macrocycles. [14] More recently, the metal ion coordinating properties of highly preorganized ligands based on the phen (see Figure 1 for key to ligand abbreviations) backbone have been reported for ligands such as PDA, [15][16][17] DPP, [18] PDALC, [19,20] and PDAM. [21] The rigidity of the phen backbone has led to widespread use of the phen moiety in ligand design.…”
Section: Introductionmentioning
confidence: 99%